Safety and Efficacy of Cryoballoon Ablation of Atrial Fibrillation in relation to the Patients’ Age: Results from a Large Real-World Multicenter Observational Project - Luigi Sciarra; Saverio Iacopino; Giuseppe Arena; Claudio Tondo; Paolo Pieragnoli; Giulio Molon; Massimiliano Manfrin; Antonio Curnis; Antonio Dello Russo; Giovanni Rovaris; Giuseppe Stabile; Leonardo Calò; et al. (Cardiology Research and Practice)
Background. The real-world efficacy and safety of atrial fibrillation (AF) ablation in particularly young and elderly patients are still under debate. The aim of the analysis was to investigate the effect of age on the efficacy and safety of cryoballoon ablation (CBA). Methods. 2,534 patients underwent pulmonary vein isolation (PVI) by way of CBA for paroxysmal or persistent drug-resistant and symptomatic AF. The population was divided into age quartiles for evaluation, including (1) <53 years, (2) ≥53 and <61 years, (3) ≥61 and <67 years, and (4) ≥67 years. Furthermore, outcomes were analyzed in patients <41 years, ≥41 and ≤74, and >74 years old. Procedural data and complications were collected, and atrial fibrillation recurrences were evaluated during follow-up. Results. Procedural-related complications (4.1%) were similar in the four subgroups according to age. At the 12-month follow-up, freedom from AF recurrence was 79.2%, 77.4%, 76.8%, and 75.2% (p=0.21), respectively (with increasing age). At 24-month follow-up, similar incidences of AF recurrence were observed in the four subgroups. When the sample was arbitrarily divided into the three age groups, a higher rate of recurrence was observed in older patients with regard to long-term follow-up (freedom from AF recurrence was 71.8% and 40.9%, respectively, at 12 and 24-month follow-up). In the univariate and multivariate analysis, age did not result in a significant predictor of AF recurrence during follow-up; however, a trend toward higher AF recurrences rates in patients ≥67 years was observed. Conclusion. The data demonstrated a high degree of safety during CBA across all patient ages. Procedural performance and complications were similar between different ages; AF recurrences seem to be more frequent in patients over 74 years.